The haemodynamic effect of an adjustable band in an arteriovenous fistula. Issue 9 (4th July 2017) - Sturm, M.; Lee, H.; Thomas, S.; Barber, T.
Abstract: A number of treatment approaches exist for excessive flowrate arteriovenous fistulae. Banding has a number of advantages, yet there is concern over its use due to reported high post-surgery thrombosis rates. A computational study is conducted of a new technique, to elucidate the hemodynamics present in the process. The key improvement involves the use of an adjustable band which can be used to optimise the flowrate during the surgery. The pressure and flowrate changes are apparent from the computational results and the computational results also demonstrate that further optimization may be possible. We then present a small cohort of five cases where the new banding procedure has been implemented with success. The new technique was combined with intra-operative ultrasound flow monitoring.